Constructing RuCoOx/NC Nanosheets with Low Crystallinity within ZIF‐9 as Bifunctional Catalysts for Highly Efficient Overall Water Splitting. Issue 17 (29th July 2021) - Tuo, Yongxiao; Liu, Wanli; Chen, Chen; Lu, Qing; Zhou, Yan; Zhang, Jun
Abstract: Electrocatalysts play a pivotal role in accelerating the sluggish electrochemical water splitting reaction. Herein, a Ru−Co oxides and carbon nitrides hybrid (RuCoOx /NC) electrocatalyst was constructed by employing ZIF‐9 to disperse Ru precursor and deliberately regulating the calcination temperature. The moderate calcination temperature results in the RuCoOx nanocomposites with small particle size and low crystallinity as well as the co‐existence of multi‐valence metal compounds, thus boosting the amount and species of active sites. Moreover, the strong interactions between Co and Ru species induce the electron transfer from Co to Ru, thus enhancing the adsorption of anion intermediates on the electron‐deficient Co species and the proton capturing capacity of electron‐sufficient Ru species. As a result, the optimized RuCoOx /NC‐350 catalyst behaved good electrocatalytic activities with 73 and 210 mV overpotential to achieve 10 mA cm −2 for HER and OER, respectively. Remarkably, it showed good durability by holding at 100 mA cm −2 for 100 h in HER and 50 mA cm −2 for 24 h in OER with small activity decline. This study may shed new light on the rational construction of highly efficient Ru‐based catalysts for electrochemical water splitting. Abstract : A RuCoOx /NC electrocatalyst with low crystallinity was constructed for overall water splitting by employing ZIF‐9 to disperse Ru precursor and deliberately regulating the calcination temperature.